Business models for product-oriented house-building companies – experience from two Swedish case studies. Issue 4 (5th October 2015) - Lessing, Jerker; Brege, Staffan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this study is to describe and analyse the business model of product-oriented house-building companies and, hence, bridging the gap of knowledge on this topic. Product-orientation implies an alternative approach to house-building, requiring new knowledge about business models and its characteristics. The balance and fit between the main business model dimensions is specifically focused on to emphasise the importance of a holistic approach. Design/methodology/approach – This study is based on a case study with two leading Swedish, product-oriented house-building companies. Semi-structured interviews with company executives, document studies, site and factory visits, along with seminars at the companies are the main data sources. Theories on business models and product orientation form the theoretical foundation for the study. Findings – The case studies describe two successful companies that used end-customer knowledge to identify a target segment, develop an offering and sequentially increase control over the production and supply chain, with limited investments. This indicates that a market-based outside-in perspective is a successful approach to establish viable house-building concepts with a balance between the business model's dimensions. Practical implications – The knowledge brought forward in this study is beneficial for practitioners that can learn about product-oriented house-building and how this must be reflected in the company's business model to be successfully applied. Social implications – The study brings forward knowledge about house-building business models that can contribute to increased house-building targeted on certain customer segments. This can be beneficial in terms of decreased costs and increased volumes of new-built, high-quality homes for a variety of customers on the market. Originality/value – Business models for product-oriented house-building companies are a scarcely covered topic in previous research, and hence, this study provides knowledge of interest for both researchers and practitioners. The case studies reveal unique information of how two companies developed their successful concepts.